Potentiating tumor immunity using aptamer-targeted RNAi to render CD8+ T cells resistant to TGFβ inhibition. (3rd April 2018) - Puplampu-Dove, Yvonne; Gefen, Tal; Rajagopalan, Anugraha; Muheramagic, Darija; Schrand, Brett; Gilboa, Eli
ABSTRACT: TGFβ secreted by tumor cells and/or tumor infiltrating stromal cells is a key mediator of tumor growth and immune suppression at the tumor site. Nonetheless, clinical trials in cancer patients targeting the TGFβ pathway exhibited at best a modest therapeutic benefit. A likely reason, a common limitation of many cancer drugs, is that the physiologic roles of TGFβ in tissue homeostasis, angiogenesis, and immune regulation precluded the dose escalation necessary to achieve a profound clinical response. Murine studies have suggested that countering immune suppressive effects of TGFβ may be sufficient to inhibit tumor growth. Here we describe an approach to render vaccine-activated CD8 + T cells transiently resistant to TGFβ inhibition using an siRNA against Smad4 to inhibit a key step in the canonical TGFβ signaling pathway. The siRNA was targeted to vaccine activated CD8 + T cells in the mouse by conjugation to a 4–1BB binding oligonucleotide (ODN) aptamer ligand (4–1BB-Smad4 conjugate). In vitro the 4–1BB-Smad4 conjugate rendered T cells partially resistant to TGFβ inhibition, and treatment of tumor bearing mice with systemically administered 4–1BB-Smad4 conjugate enhanced vaccine- and irradiation-induced antitumor immunity. Limiting the inhibitory effects of TGFβ to tumor-specific T cells will not interfere with its multiple physiologic roles and hence reduce the risk of toxicity.